An evaluation of the effectiveness of Critical Biodiversity Areas, identified through a systematic conservation planning process, to reduce biodiversity loss outside protected areas in South Africa. (April 2022) - von Staden, Lize; Lötter, Mervyn C.; Holness, Stephen; Lombard, Amanda T.
Abstract: Systematic Conservation Planning (SCP) is a spatially explicit process used globally to prioritize conservation actions, but its effectiveness is difficult to quantify. In South Africa, terrestrial SCP processes are mainly used to identify important biodiversity areas outside of formal protected areas that are required to meet conservation targets. Environmental policy refers to these areas as Critical Biodiversity Areas (CBAs), and uses them to inform land use change decisions. Using Mpumalanga Province as a case study, avoided loss within CBAs is quantified using counterfactual matching methods. To contextualize the results, it is benchmarked against avoided loss achieved by protected areas during the same period. Significant reductions of 54–72% in land clearing were achieved in CBAs compared to other natural areas and were comparable to avoided loss achieved by protected areas in similar evaluations in other countries. Protected areas in Mpumalanga were found to be very effective (88% relative avoided loss) but are located in areas of lower land use change pressures than CBAs. Avoided loss was quantified as 1058 ha for Irreplaceable CBAs, 5285 ha for Optimal CBAs and 20, 586 ha for protected areas. The consideration of biodiversity priorities in land use change decisions outside protected areas was found to be an effective complementary strategy to protected areas to avoid loss of biodiversity in areas typically not available for protected area expansion. Highlights: Counterfactual methods are used to evaluate the outcome of a systematic conservation planning process. Loss of biodiversity priority areas was reduced by 54-72% over a 10-year period in Mpumalanga Province. Effectiveness estimates rank highly among other spatially explicit conservation interventions. Consideration of biodiversity priorities in land use decisions complements protected areas.